Pengaruh Penambahan Aluminium Oksida Terhadap Kekerasan dan Struktur Mikro Paduan Mg-Sn - Ayuda Darmawan Yulianto; Muhammad Reza Parega; Kusharjanto Suhirman; Supono Adi Dwiwanto (Jurnal Metalurgi dan Material Indonesia, 2018)
This paper focused on hardness and microstructure of Mg-Sn alloy by Aluminium Oxide addition. Mg-Sn alloys were prepared by casting with the addition of Aluminium Oxide from 1% to 5%wt, then quenching to the water. The microstructure evolution and hardness were investigated. Based on hardness test result the hardness was increased. With 1% to 5% Aluminium Oxide addition, hardness increased from 22.9 BHN to 30.8 BHN. The highest hardness was in the addition of 5% Aluminium Oxide with 30.8 BHN. The result showed that increasing of Aluminium Oxide content resulted the globular and smaller grains.